The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1007/s001130050477
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and incidence of the rupture of the posterior cruciate ligament

Abstract: The purpose of this article is to evaluate the incidence and to give a general review of the examination of the posterior ligament complex. At least ca. 8-10 % of all severe ligament injuries concern the posterior cruciate ligament, which means, that an estimated 4,000-5,000 Germans suffer a PCL rupture every year. Motor-vehicle accidents are the most common cause of the injury, but sports-related traumas (football, skiing) have increased in recent years. The high number of high-energy mechanisms involved (up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…Patients injured in highenergy motor vehicle accidents suffer a higher incidence of additional life-threatening injuries, and therefore ligamentous knee injuries can be easily overlooked. A combined injury (PCL and PLS) is frequent, particularly in traffi c accidents, but can also occur in 50 % of athletic injuries [ 14 ].…”
Section: Epidemiology and Mechanisms Of Sports-related Pcl Injurymentioning
confidence: 99%
“…Patients injured in highenergy motor vehicle accidents suffer a higher incidence of additional life-threatening injuries, and therefore ligamentous knee injuries can be easily overlooked. A combined injury (PCL and PLS) is frequent, particularly in traffi c accidents, but can also occur in 50 % of athletic injuries [ 14 ].…”
Section: Epidemiology and Mechanisms Of Sports-related Pcl Injurymentioning
confidence: 99%
“…Hochstein et al (1999) reported that an estimated 4000-5000 Germans suffer PCL injuries each year with a mean age of 27.5 AE 9.9 years. In the context of the trauma setting, the most common causes are motor vehicle collisions followed by sporting injuries.…”
Section: Mechanisms Of Injury and Epidemiologymentioning
confidence: 99%
“…Die hintere Kreuzbandverletzung ist eine häufig übersehene und komplexe Verletzung, was sich in einer umfangreichen Klassifikation nach Cooper zeigt [6]. So beträgt der Anteil chronischer dorsaler Instabilitäten im Patientengut verschiedener Autoren bis zu 70 % [7], und eine Serie operativ behandelter Instabilitäten zeigte im Mittel einen Abstand von 3,8 Jahren zum Unfallereignis (1 bis 8 Jahre) [3,7,8]. Die übersehene hintere Kreuzbandverletzung kann zu einer fixierten hinteren Schublade führen, wenn z.…”
Section: Introductionunclassified